Dual Role of FtsH in Regulating Lipopolysaccharide Biosynthesis in Escherichia coli - Katz, Chen (American Society for Microbiology (ASM), 2008)
In Escherichia coli, FtsH (HflB) is a membrane-bound, ATP-dependent metalloendoprotease belonging to the AAA family (ATPases associated with diverse cellular activities). FtsH has a limited spectrum of known substrates, including the transcriptional activator σ(32). FtsH is the only known E. coli protease that is essential, as it regulates the concentration of LpxC, which carries out the first committed step in the synthesis of lipid A. Here we identify a new FtsH substrate—3-deoxy-d-manno-octulosonate (KDO) transferase—which carries out the attachment of two KDO residues to the lipid A precursor (lipid IV(A)) to form the minimal essential structure of the lipopolysaccharide (LPS) (KDO(2)-lipid A). Thus, FtsH regulates the concentration of the lipid moiety of LPS (lipid A) as well as the sugar moiety (KDO-based core oligosaccharides), ensuring a balanced synthesis of LPS.